The Usage of Kinship Terms and Their Values among Acehnese People in Indonesia - Idaryani, Idaryani; Fidyati, Fidyati (Journal of English Language and Education, 2023)
This paper explores the use of kinship terms of Acehnese and their values among Acehnese people. The data for this paper was obtained based on the result of the interview from ten participants living in the two suburbs of Lhokseumawe City. The participants of the study were five female participants from Rayeuk Karung village and five participants from Blang Punteuet village, Lhokseumawe City, Aceh Province, Indonesia. All participants’ age ranged from 60 to 85 years old. The result of the study showed that kinship terms used by Acehnese people can be classified into following categories; First, the Acehnese language has more than one term of a kin to address for a kin relation either in consanguineal or affinal relations, and the usage terms of kin varies based on consanguineal and affinal relations between the core family member and extended family member. Second, the use of kinship terms is based on affinal and consanguineal relations, sex, birth order, and social status. Third, the usage of kinship terms based on the affinal and the consanguineal relations are bilateral or overlapping except for the five specific terms of kinship.  Fourth, some kinship terms of affinal relation are added with a specific adjective, and specific phrases are used for kindship terms both for affinal and consanguineal relations. Five, the use of kinship terms by Acehnese people has cultural and historical values as part of the crucial construction of Acehnese identity.